การวิเคราะห์ประเด็นข้อมูลหลักสำหรับการออกแบบโปรไฟล์นักเรียนหรับการจัดการศึกษาแบบเรียนรวม - นุตโร เจนจิรา; ศรีเคลือบ กนิษฐ์; โอภาสเกียรติกุล วาทินี (An Online Journal of Education, 2018)
This study aims to analyze the major data collection which is essential for inclusive education and recent type of students’ data collection in each issue. The population in this study is 66 elementary teachers. The tool used is a questionnaire for teachers about students’ data collection for inclusive education. The findings revealed that the result of survey about the opinion towards inclusive education needs. Most teachers thought that it is necessary to most necessary about the necessity of students’ data collection. The average is 30 – 97 which reflects that the teachers realized the importance of collecting students’ data each point. Yet, there is a proportion of collecting data about type of data collection in each point, and is not the data collection at the nearly same level. Thus, the researcher selected major data issue for designing to 11 issues from four aspects of information, such as academic and learning of students, social and personal development, physical development, and needs management.